Feasibility study of the immunogenicity and safety of a novel DTPw/Hib (PRP-T) Brazilian combination compared to a licensed vaccine in healthy children at 2, 4, and 6 months of age - SueAnn Costa Clemens; Tania Azevedo; Akira Homma (Revista da Sociedade Brasileira de Medicina Tropical, 2003)
Vaccination of infants with conjugated Haemophilus influenzae type b (Hib) vaccines has been proven to reduce Hib meningitis by 95% and pneumoniae by 20%. The routine use of Hib vaccine is facilitated by the introduction of combination vaccines into the EPI (Expanded Plan of Immunization). The objective of this study was to compare the immunogenicity and reactogenicity of an extemporaneously mixed DTPw/Hib (diphtheria-tetanus-whole cell pertussis) combination, using the technology of two Brazilian manufacturers, against a licensed DTPw/Hib European combination in 108 infants vaccinated at 2, 4 and 6 months according to the local national schedule. The Brazilian combination was highly immunogenic with Hib seroprotection rates (anti-PRP > 0.15 mg /ml of 98% after 2 doses and 100% after 3). Also for tetanus and pertussis the new Brazilian combination was as immunogenic as the European counterpart, except the diphtheria seroprotection rates and titers were lower. There was also no clinically relevant difference in reactogenicity. If these feasibility results are confirmed, the Brazilian DTPw/Hib combination should help to boost the uptake of Hib vaccination in Brazil.